INFLUENCE OF SOME ANATOMICAL FEATURES ON THE DENSITY OF WOOD - Bardarov, Nikolay; Novoselets, Catherine (Innovation in Woodworking Industry and Engineering design, 2013)
The wood of coniferous trees is characterized by simple and orderly structure. Within the annual ring the traheids are sealed and thickened. The work examines the relationships between anatomical characteristics of wood and its density. The traheids have been examined in the wood of the spruce. Traces in the dimensional change in the annual ring have been measured successively from the earliest to the latest. The studied wood is divided into groups with narrow and wide rings. A comparison is made between the values for individual groups to seek relationships between anatomical structure and the density of wood.